The influence of fines in sandstones on the performance of concrete. (2022) - Sharma, Prashant; Kumar Parashar, Arun; Sharma, Neha
Abstract: As sand pits are exhausted and dredging is forbidden by environmental rules, construction materials are increasingly scarce. As a result, we've had to hunt for a new and feasible choice. This proposed study makes a concerted effort to give a practical solution to this problem. Manufactured sand, which is used as a fine aggregate in concrete, is made from sandstone. River sand has been totally replaced by M−Sand, which contains micro particles. Micro fines are particles with a length and diameter of less than 75 µm. Micro fines are utilised in various amounts in the manufacturing of M30 grade concrete (0 percent, 5 percent, 10 percent, 15 percent, 20 percent, and 25 percent). For the aim of testing and comparing, six manufactured sand mixtures and one river sand mix were constructed. The compressive strength of produced sand was found to be improved when the proper amount of micro particles were added.